Size Distribution of Colistin Delivery by Different Type Nebulizers and Concentrations During Mechanical Ventilation - Ching-Yi Liu; Hsin-Kuo Ko; James B. Fink; Gwo-Hwa Wan; Chung-Chi Huang; Yu-Chun Chen; Hui-Ling Lin (MDPI AG, 2019)
Although aerosol delivery through mechanical ventilators has been used to administer various medications, little is known of administration with colistin. This in vitro evaluation aimed to evaluate size distribution of colistin delivery by different types of nebulizers and concentrations during mechanical ventilation. Colistin methanesulfonate (colistin) for injection was dissolved in 6 mL of distilled water to produce a low concentration (L; 156 mg) and a high concentration (H; 312 mg). A dose volume of 6 mL was placed in a vibrating mesh nebulizer (VMN) and a jet nebulizer (JN). The inhaled mass (mean ± SD) of the VMN-L (53.80 ± 14.79 mg) was greater than both the JN-L (19.82 ± 3.34 mg, P = 0.001) and JN-H (31.72 ± 4.48 mg, P = 0.017). The nebulization time of the VMN-L (42.35 ± 2.30 min) was two times longer than the JN-L (21.12 ± 0.8 min) or JN-H (21.65 ± 0.42 min; P < 0.001). The mass median aerodynamic distal to the endotracheal tube was within a similar range at 2.03 to 2.26 μm (P = 0.434), independent of neb or formulation concentration. In conclusion, the VMN-L yields greater inhaled mass than the JN with either concentration. Therefore, a standard nominal dose of colistin results in a higher delivered dose during mechanical ventilation with a VMN compared with a JN and may be considered the preferred device. If JN must be used, multiple doses of low concentration colistin may compensate for poor delivery performance.